Photocatalytic Activity Induced by Metal Nanoparticles Synthesized by Sustainable Approaches: A Comprehensive Review - Krishna, Prashanth Gopala; Chandra Mishra, Prabhu; Naika, Mutthuraju Mahadev; Gadewar, Manoj; Ananthaswamy, Prashanth Paduvarahalli; Rao, Srilatha; Boselin Prabhu, Sivadhas Rosejanet; Yatish, Kalanakoppal Venkatesh; Nagendra, Holenarasipura Gundurao; Moustafa, Mahmoud; Al-Shehri, Mohammed; Jha, Saurabh Kumar; et al. (Frontiers in Chemistry, 2022)
Synthesis of nanoparticles from plant extracts has become a very popular study subject in recent decades due to various advantages such as easy and low-cost synthesis, excellent product stability, and environmental friendliness, among others. Furthermore, plant extract nanoparticles have a variety of applications, including catalyst, photocatalyst, magnetic property, antibacterial activity, cytotoxicity, CT-DNA binding, sensing, and so on. For the creation of nanoparticles, scientists employ a variety of methods. Nanoparticle synthesis using green technologies is the simplest and most environmentally friendly of all the processes. Several microorganisms, such as bacteria, fungus, and plant components, are used in green techniques. We cover the synthesis of several metal nanoparticles using diverse plant extracts, as well as their characterizsation by UV-visible, XRD (X-Ray Diffraction), SEM (Scanning Electron Microscope), TEM (Transmission Electron Microscope), FTIR (Fourier Transform Infrared Spectroscopy technique) in this review article. Further, we discuss in detail the photo catalytic activity of these nanoparticles.